A Facile Route to Fabricate CS/GO Composite Film for the Application of Therapeutic Contact Lenses. (10th February 2020) - Chen, Pin; Wang, Xin; Kong, Jingyang; Hu, Xiaohong
Abstract : Traditional contact lenses bring convenience for ophthalmic drug delivery. However, either as contact lenses or as drug carriers, traditional materials have still some drawbacks in the field. Therefore, a transparent film was designed and investigated for the application of therapeutic contact lenses. Chitosan (CS)/graphene oxide (GO) composite film and CS film were fabricated with acceptable transparent and tensile properties by simple casting flow method. Although swelling ratio of CS/GO composite film was higher than that of CS film with significant difference, both formed films had suitable swelling ratio for contact lens application. Both CS/GO composite film and CS film exhibited typical CS infrared characteristic peaks. CS/GO composite film had significant greater breaking strength than CS film, but its elongation at break was a little lower than CS film. Either CS/GO composite film or CS film exhibited good hydrophilic property with a contact angle of around 20 degree. Ofloxacin as a model drug was loaded into films by adsorption diffusion method. Loaded drug amount in CS/GO composite film was a little larger than that in CS film, but without significant difference. The drug release behaviors from CS/GO composite film or CS film were investigated and revealed that the loaded drug could be controlled to release in the first hour. Two kinds of cells were used to evaluate the biocompatibility of films by in vitro method. It was found that both CS/GO composite film and CS film could support human umbilical vein endothelial cell (HUVEC) growth. But for human epidermal fibroblasts (HSF) cells, CS/GO composite film could promote HSF cells growth and proliferation much better than CS film.